Development of curriculum in Community Pediatrics for fourth-year medical students at Angeles University Foundation - Lopez, Maria Lita L.; Fajutagana, Nemuel S. (Manila National Teacher Training Center for the Health Professions, University of the Philippines Manila, 2024)
This capstone project on community pediatrics for 4th-year medical students, emphasise the pivotal role of community service in addressing the health needs of children and families within diverse communities. This program focuses on holistic healthcare delivery, encompassing health promotion, preventive care, family support, and advocacy.

Through community-based initiatives, students engage in hands-on experience to develop the knowledge, skills and attitudes in becoming a community pediatrics. The students can collaborate with community partners, schools, and organisations to promote child health and well-being, and advocate for equitable access to healthcare services.

The curriculum integrates theoretical knowledge with practical experience, including health promotion activities, preventive screenings, family-centered care, and cultural competency training. Students participate in program evaluations, and emergency preparedness activities to enhance skills and contribute to evidence-based practice.

By fostering a commitment to service, advocacy, and collaboration, this capstone program prepares medical students to become compassionate, culturally competent, and socially responsible healthcare professionals equipped to address the complex health challenges facing communities.
Capstone Project
Keywords: Curriculum development; Community pediatrics